Association between myocardial wall thickness and left ventricular functional recovery after catheter ablation of atrial fibrillation in patients with reduced ejection fraction. (14th October 2021) - Okada, M; Tanaka, N; Tanaka, K; Hirao, Y; Harada, S; Onishi, T; Koyama, Y; Okamura, A; Iwakura, K; Fujii, K; Inoue, K
Abstract: Background: Catheter ablation of atrial fibrillation (AFCA) is an effective treatment to develop left ventricular (LV) functional recovery. However, the degree of recovery differs between individuals due to the different extent of myocardial fibrosis and scarring. Purpose: To examine whether pre-ablation LV wall thickness (WT) and its regional heterogeneity predict LV functional recovery after AFCA in patients with LV systolic dysfunction. Methods: Of 3682 consecutive patients who underwent first-time AFCA between January 2012 and September 2020 in our institution, 174 (age, 63±10 years; male, 83%; ischemic cardiomyopathy, 14%) with a baseline LV ejection fraction (LVEF) of <40% were retrospectively evaluated. They were subjected to 256-slice MDCT scanning at baseline and 3 months after AFCA. Baseline WT was evaluated by 16-segment model. Mean and standard deviation (SD) of 16 regional WT were calculated in both end-systolic and end-diastolic phase. Results: LVEF significantly improved from 30±7% to 57±17% (p<0.001) after AFCA. Increase in LVEF (delta-LVEF) was positively correlated with baseline end-diastolic WT (r=0.31, p<0.001) and negatively correlated with SD of end-systolic WT (r=−0.21, p=0.007). Independent of WT measurements, delta-LVEF was negatively correlated with LV end-diastolic volume (r=−0.42, p<0.001). We created a scoring system to predict the degree of wall motion recovery using the median value of the 3 variables; assigned 1 point each for end-diastolic WT >7.4mm, SD of end-systolic WT <1.61mm, and LV end-diastolic volume <125ml. The model successfully predicted improvement in LVEF after AFCA (0 point (N=13) vs. 1 point (N=72) vs. 2–3 point (N=89), 11±16% vs. 20±17% vs. 33±12%, p<0.001). Conclusion: Myocardial WT and its regional heterogeneity as well as LV end-diastolic volume predicted functional recovery after AFCA in patients with reduced LVEF. Funding Acknowledgement: Type of funding sources: None.